2020
DOI: 10.1371/journal.pone.0240940
|View full text |Cite
|
Sign up to set email alerts
|

Maximising the clustering coefficient of networks and the effects on habitat network robustness

Abstract: The robustness of networks against node failure and the response of networks to node removal has been studied extensively for networks such as transportation networks, power grids, and food webs. In many cases, a network's clustering coefficient was identified as a good indicator for network robustness. In ecology, habitat networks constitute a powerful tool to represent metapopulations or-communities, where nodes represent habitat patches and links indicate how these are connected. Current climate and land-us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Hence, the cardinality of N ( v ), also known as the degree of node v , expresses the number of neighbors of node v and can be written as | N ( v )| = k v , where k v is the degree of node v . A clique of three nodes { u , v , w }, where ( u , v ), ( u , w ), ( v , w ) ∈ E are links that connect all three nodes, is a triangle in a network G [ 38 ]. Let T ( v ) = |{( u , w ); w , u ∈ N ( v ), ( u , w ) ∈ E }| be the number of triangles formed with the center at node v .…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the cardinality of N ( v ), also known as the degree of node v , expresses the number of neighbors of node v and can be written as | N ( v )| = k v , where k v is the degree of node v . A clique of three nodes { u , v , w }, where ( u , v ), ( u , w ), ( v , w ) ∈ E are links that connect all three nodes, is a triangle in a network G [ 38 ]. Let T ( v ) = |{( u , w ); w , u ∈ N ( v ), ( u , w ) ∈ E }| be the number of triangles formed with the center at node v .…”
Section: Methodsmentioning
confidence: 99%
“…For community detection algorithms, the modularity score comes very little in bipartite networks, which leads to a very sparse relationship between entities of the same community. The clustering coefficient of small bipartite networks is also a not significant measure to find the strength of clusters (Heer et al 2020 ). Thus, an integrated model gets developed to optimize the results for both modularity and clustering.…”
Section: Preliminariesmentioning
confidence: 99%
“…The clustering coefficient is a measurement of the density of each vertex's 1.5-degree egocentric network. The clustering coefficient is high for dense linkages between nodes (Heer et al 2020 ; Chessa et al 2014 ). For example, in a friendship network, if all friends know each other very well, its clustering coefficient will be high.…”
Section: Embm Algorithm Of Bipartite Weighted Networkmentioning
confidence: 99%
“…Different approaches to evaluate network robustness have been developed in the literature (Jiang et al 2014, Aerts et al 2016, Bellingeri and Cassi 2018, Bellingeri et al 2019, Farooq et al 2020, Freitas et al 2020, Heer et al 2020, Rachdi et al 2020, Williams and Patterson 2020, Stacey et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Williams and Patterson (2020) analyzed a global network of associations between coral species and Symbiodiniaceae; they used the concept of ecological robustness, defined by the amount of perturbation needed to decrease the number of nodes by 50%, and evaluated it using different node removal models. Heer et al (2020) used habitat networks to evaluate the habitat loss and to which extent it was possible to modify networks to obtain higher robustness; they suggested that the clustering coefficient was identified as a good indicator for network robustness and, specifically, they developed tools to identify which links should be added to the network to increase its robustness. Freitas et al (2020) presented a robustness analysis of an inter-cities mobility complex network, where cities are represented by nodes and the flow of people via terrestrial transports by links; they systematically isolated nodes either random or guided by specific strategies, and assessed the impact of these perturbations with different metrics.…”
Section: Introductionmentioning
confidence: 99%